A Bioinspired Nanoprobe with Multilevel Responsive T1‐Weighted MR Signal‐Amplification Illuminates Ultrasmall Metastases. Issue 4 (4th December 2019) - Li, Yao; Zhao, Xiao; Liu, Xiaoli; Cheng, Keman; Han, Xuexiang; Zhang, Yinlong; Min, Huan; Liu, Guangna; Xu, Junchao; Shi, Jian; Qin, Hao; Fan, Haiming; et al.
Abstract: Metastasis remains the major cause of death in cancer patients. Thus, there is a need to sensitively detect tumor metastasis, especially ultrasmall metastasis, for early diagnosis and precise treatment of cancer. Herein, an ultrasensitive T 1 ‐weighted magnetic resonance imaging (MRI) contrast agent, UMFNP‐CREKA is reported. By conjugating the ultrasmall manganese ferrite nanoparticles (UMFNPs) with a tumor‐targeting penta‐peptide CREKA (Cys‐Arg‐Glu‐Lys‐Ala), ultrasmall breast cancer metastases are accurately detected. With a behavior similar to neutrophils' immunosurveillance process for eliminating foreign pathogens, UMFNP‐CREKA exhibits a chemotactic "targeting‐activation" capacity. UMFNP‐CREKA is recruited to the margin of tumor metastases by the binding of CREKA with fibrin‐fibronectin complexes, which are abundant around tumors, and then release of manganese ions (Mn 2+ ) to the metastasis in response to pathological parameters (mild acidity and elevated H2 O2 ). The localized release of Mn 2+ and its interaction with proteins affects a marked amplification of T 1 ‐weighted magnetic resonance (MR) signals. In vivo T 1 ‐weighted MRI experiments reveal that UMFNP‐CREKA can detect metastases at an unprecedented minimum detection limit of 0.39 mm, which has significantly extended the detection limit of previously reported MRI probe. Abstract : An ultrasensitive T 1 ‐weighted magnetic resonance imaging contrast agent, UMFNP‐CREKA, is presented to accurately detect ultrasmall breast cancer metastases. UMFNP‐CREKA exhibits multilevel responsive T 1 magnetic resonance (MR) signal‐amplification capacity in response to overall features of the metastasis microenvironment (mild acidity and elevated H2 O2 ). As a result, UMFNP‐CREKA can detect metastases at an unprecedented minimum detection limit of 0.39 mm.